THE CHARACTERIZATION OF SIMPLISIA, ISOLATION AND IDENTIFICATION OF CHEMICAL CONSTITUENS FROM THALLUS Turbinaria decurrens Bory - Irma Sari (Universitas Syiah Kuala, 2015)
The characterization of simplisia, phytochemical screening, extraction, isolation and identification of chemical constituens from thallus Turbinaria decurrens Bory have been carried out. The examination of simplisia characteristics gave the water soluble extract the value of 10.59%, ethanol soluble extract valued at 0.93%, total ash valued at 15.64%, the acid insoluble ash value 0.79% and the water content valued at 8.66%. The result of phytochemical screening showed that there was triterpens/steroids present. The extraction process was carried out by percolation and then was separated by liquid vacum column chromatography. Then by preparative thin layer chromatography isolate B1 was obtained. The analysis of isolate B1 by infra red spectrophotometry showed hydroxyl, aliphatic C-H bond, C=O bond, double bond of C=C, C=O bond, C=H bond of CH3 and CH2, were present. Ultra violet spectrophotometry exhibited a maximum absorption at 242 nm and mass spectrometric fragmentation pattern exhibited that the molecular weight of isolate B1 was 394, it was suspected ergosta -4,7,22 –trien -3 one.